2014
DOI: 10.1021/ol501256d
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Carbene Catalyzed Umpolung of Styrenes: Mechanistic Elucidation and Selective Tail-to-Tail Dimerization

Abstract: The reaction between N-heterocyclic carbenes (NHCs) and styrenes yields alkyl-substituted azolium salts, which are able to form nucleophilic deoxy Breslow intermediates by simple deprotonation. This hitherto unknown reaction of NHCs represents a new way to generate deoxy Breslow intermediates and paves the way for the selective NHC-catalyzed tail-to-tail homodimerization of styrenes. This reaction significantly broadens the scope of the Michael umpolung and provides a new method to generate 1,4-diaryl compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…Subsequently, analogous dimerization of methacrylonitrile [29] and styrenes [30] has also been recently realized by the Matsuoka and Glorius groups, respectively. Subsequently, analogous dimerization of methacrylonitrile [29] and styrenes [30] has also been recently realized by the Matsuoka and Glorius groups, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, analogous dimerization of methacrylonitrile [29] and styrenes [30] has also been recently realized by the Matsuoka and Glorius groups, respectively. Subsequently, analogous dimerization of methacrylonitrile [29] and styrenes [30] has also been recently realized by the Matsuoka and Glorius groups, respectively.…”
mentioning
confidence: 99%
“…other methacrylates typically at 80 8C, whereas the common imidazolylidene carbenes are ineffective. Subsequently, analogous dimerization of methacrylonitrile [29] and styrenes [30] has also been recently realized by the Matsuoka and Glorius groups, respectively. Switching to I i Pr (1,3-di-isopropylimidazolin-2-ylidene), Taton et al recently found that MMA is cyclodimerized to an imidazolium enolate cyclodimer.…”
mentioning
confidence: 99%
“…[21] To realize catalytic CÀCb ond-forming CS N Ar reactions,w e envisioned the use of N-heterocyclic carbene (NHC) catalysts,w hich can be used to generate an ucleophile from ac arbonyl compound or an alkyl halide in ac atalytic manner. [22][23][24] Among the several precursors that can be activated by an NHC catalyst, we opted to use a,b-unsaturated carbonyl compounds,which are known to serve as latent b-carbanions via umpolung.A lthough the generation of this type of nucleophile has been utilized in several NHCcatalyzed reactions [25] since the first report by Fu and coworkers, [26] its use in catalytic aromatic substitution reactions has not been accomplished. [27,28] We used an aryl fluoride bearing an a,b-unsaturated amide,w hich would undergo an aromatic substitution reaction by acatalytically generated bcarbanion (Scheme 1b).…”
mentioning
confidence: 99%
“…[6] Moreover,N HCs are employed for the conjugate umpolung of enals for the generation of homoenolate equivalents. [8a] Moreover,efficient tail-to-tail dimerization of methacrylates by the NHC-catalyzed umpolung of Michael acceptors were demonstrated independently by the groups of Matsuoka [9] and Glorius [10] (Scheme 1c). [8a] Moreover,efficient tail-to-tail dimerization of methacrylates by the NHC-catalyzed umpolung of Michael acceptors were demonstrated independently by the groups of Matsuoka [9] and Glorius [10] (Scheme 1c).…”
mentioning
confidence: 99%
“…[7] In the majority of cases,t he umpolung using NHCs is limited to aldehydes.I n 2006, Fu and co-workers extended the umpolung concept to Michael acceptors for the synthesis of cyclic a,b-unsaturated esters by an intramolecular b-alkylation (Heck-type reaction; Scheme 1b). [8a] Moreover,efficient tail-to-tail dimerization of methacrylates by the NHC-catalyzed umpolung of Michael acceptors were demonstrated independently by the groups of Matsuoka [9] and Glorius [10] (Scheme 1c). [11] Thea ddition of NHCs to alkyl halides leading to the generation of the deoxy-Breslow intermediates was demonstrated by the groups of Jacobi von Wangelin [12] and Mayr.…”
mentioning
confidence: 99%